TRIAS POLITICA DALAM PERSPEKTIF FIKIH SIYASAH - Wery Gusmansyah (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2017)
According to the concept of the trias politica Montesquieu, in every government there are three kinds of powers, namely the legislative power, the executive power, on matters pertaining to the law of nations; and judicial power on matters that depend on civil law